Sowing the Seeds of The Message: Islamist Women Activists Before, During, and After the Egyptian Revolution. Issue 1 (31st December 2020) - Abdel-Fadil, Mona
Abstract: This article focuses on the activities and experiences of a group of Islamist women activists, socialized within the ranks of Islam Online Arabic (IOL). These activists engaged in a range of significant social, political, and media practices, before, during and after the ousting of Mubarak; as individuals, as journalists, as counsellors, as agenda setters and creators of media campaigns. Drawing on longitudinal and ethnographic research, this article is able to highlight and document the continuities in modes of civic engagement and activism across multiple media platforms, organizations, and time. It demonstrates how these women's activism continues to be framed by the (IOL) trope the message, which entails cultivation of self, social, and political awareness. The Egyptian revolution is theoretically conceptualized as a phase of liminality (Turner 1979). Liminality entails upheaval, fear, and promise. The article draws attention to the gendered experiences of the revolution including circumvention of patriarchal structures and the re-negotiations of gender norms. Upon conclusion, it is argued that the message has proven highly adaptable to shifting political scenarios. Indeed, the betwixt and between stage of liminality that Egypt was thrust into after the ousting of Mubarak, was particularly fertile soil for sowing and reaping the seeds of the message.